Subsequent Precedence: Milton's Materialistic Reading of Ficino and Tasso - Grossman, Marshall (Surfaces, 1996)
In departing from Bill Readings' view that Milton's work inaugurated modernist history as lacking an inaugurating event, this essay engages the metaleptic articulation of origin and terminus, meaning and signifier, in some of Milton's prose and explores the rhetorical performance of Plato's idea of the icastic imagination, which convinced Milton that writing poetry is socially productive labor.